Recurrent Focal Segmental Glomeruloscleosis Progressing to Collapsing Glomerulopathy in Renal Graft of an Autopsy study. (28th October 2021) - Thorburn, C; Jabbar, K J; Li, W; Kanaan, H; Zhang, P
Abstract: Introduction/Objective: Collapsing glomerulopathy (CGN) mainly occurs in patients of African descent because a majority of these patients have APOL-1 gene mutations that results in damage of terminally differentiated podocytes, diffuse fusion of foot processes, and podocyte hyperplasia. Idiopathic FSGS is associated with high rates of recurrent FSGS in renal transplants and can be seen in patients with APOL-1 gene mutations as well, but recurrent FSGS progressing to CGN is not reported. Here we report an autopsy case with renal transplant showing recurrent FSGS progressing to CGN. Methods/Case Report: Our patient was a 32 year old African American man who had a native renal biopsy which showed primary FSGS (with no infectious history) 8 years ago. Last year he received a renal transplantation (complex donor kidney from a deceased 25 year old man with pre-mortem serum creatinine (sCr) at 0.7 mg/dl). His initial post- transplant sCr level was as low as 1.17 mg/dl. However, in 4 months his sCr went up and he began to have higher levels of proteinuria. Sequential biopsies indicated that the patient developed a recurrent FSGS that progressed to show features of CGN. In his autopsy kidney graft, approximately 50% of glomeruli show collapsed loops with various degrees of hyperplasic podocytes, confirmed by positive CD133 staining (a progenitor cell marker). In addition, the hyperplastic podocytes lost WT-1 expression and were positive for Ki-67 staining. Distal tubules showed obvious cystic dilation. Overall findings were consistent with a severe form of CGN. Results (if a Case Study enter NA): NA Conclusion: The clinical presentation of recurrent FSGS progressing to collapsing FSGS in our patient suggests that CGN and idiopathic FSGS may share a common pathophysiologic mechanism of disease.